2020
DOI: 10.1016/j.isci.2020.101649
|View full text |Cite
|
Sign up to set email alerts
|

AXL Is a Driver of Stemness in Normal Mammary Gland and Breast Cancer

Abstract: Summary The receptor tyrosine kinase AXL is associated with epithelial plasticity in several solid tumors including breast cancer and AXL-targeting agents are currently in clinical trials. We hypothesized that AXL is a driver of stemness traits in cancer by co-option of a regulatory function normally reserved for stem cells. AXL-expressing cells in human mammary epithelial ducts co-expressed markers associated with multipotency, and AXL inhibition abolished colony formation and self-maintenance acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…To investigate whether epithelial progenitors from HR epithelia exhibited differentiation biases, we performed clonal differentiation assays on receptor tyrosine kinase cKit (CD117)-expressing cells enriched by FACS. Mammary epithelial cells enriched for high expression of cKit are capable of multilineage differentiation, but there is a luminal bias 7,22 . After FACS enrichment, cKit + cells were attached to cover slips at clonal density, and daughter cells in the resulting colonies were assayed by immunofluorescence for the differentiation markers KRT14 and KRT19 after either 2 d or 7 d. Marker-based watershed segmentation identified single cells in images, followed by measurement of the mean fluorescent signal that corresponded to KRT14 or KRT19 expression.…”
Section: Hr Progenitors Have Differentiation Defects and A Basal Biasmentioning
confidence: 99%
“…To investigate whether epithelial progenitors from HR epithelia exhibited differentiation biases, we performed clonal differentiation assays on receptor tyrosine kinase cKit (CD117)-expressing cells enriched by FACS. Mammary epithelial cells enriched for high expression of cKit are capable of multilineage differentiation, but there is a luminal bias 7,22 . After FACS enrichment, cKit + cells were attached to cover slips at clonal density, and daughter cells in the resulting colonies were assayed by immunofluorescence for the differentiation markers KRT14 and KRT19 after either 2 d or 7 d. Marker-based watershed segmentation identified single cells in images, followed by measurement of the mean fluorescent signal that corresponded to KRT14 or KRT19 expression.…”
Section: Hr Progenitors Have Differentiation Defects and A Basal Biasmentioning
confidence: 99%
“…It has been reported that while AKT1 and AKT2 are found in the cytoplasm and mitochondria, respectively, AKT3 is often found in the nucleus (29). We observed clear nuclear localization of AKT3 in MDA-MB-231 and MCF10A/slug cells (30) (Supplemental Figure 3A,B). Interestingly, AXL silencing in MCF10a/slug cells reduced AKT3 nuclear localization, suggesting that AXL mediates the nuclear localization of AKT3 (Supplemental Figure 3B).…”
Section: Resultsmentioning
confidence: 92%
“…This effect of WNK1 was independent of OSR1. AXL expression is associated with metastasis and poor prognosis in a variety of tumor types including breast cancer (40,47,53,54). BGB324 is a first-in-class AXL inhibitor, currently in phase II clinical trials, exhibiting promising therapeutic characteristics.…”
Section: Discussionmentioning
confidence: 99%